Surgical treatment coarctation of the aorta in a premature newborn weighing 800 g - B.M. Todurov; V.G. Karpenko; V.Y. Vashkeba; V.V. Sakalov; O.A. Lastochkina; I.V. Galamay; V.B. Demyanchuk (Кардіохірургія та інтервенційна кардіологія)
Surgical treatment of coarctation of the aorta in newborns is considered a highly effective method, which can be used in almost all anatomical forms of malformation. However, extremely low birth weight may present an obstacle for the successful treatment, both during surgery and in the postoperative period. We present a case of surgical correction of aortic coarctation in a premature newborn patient weighing 800 g. A 16-day-old patient was transported to the clinics by an ambulance team with a diagnosis of critical preductal coarctation of the aortic isthmus, open ductus arteriosus, grade 2 malnutrition, grade IIB heart failure. At the time of hospitalization, the condition of the child was regarded as severe due to severe heart and respiratory failure. Due to the serious condition of the patient, it was decided to perform a resection of coarctation of the aorta, despite the critically low body weight of the child. The postoperative period was uneventful. On the 15th day, the patient was transferred to the regional children's hospital in stable condition. This case suggests that surgical treatment of aortic coarctation remains a gold standard of the treatment in premature infants.